Distinct phenotype of neutrophil, monocyte, and eosinophil populations indicates altered myelopoiesis in a subset of patients with multiple myeloma - Ong, Krystle L.; Davis, Marcus D.; Purnell, Kalyn K.; Cutshall, Hannah; Pal, Harish C.; Connelly, Ashley N.; Fay, Christian X.; Kuznetsova, Valeriya; Brown, Elizabeth E.; Hel, Zdenek (Frontiers in Oncology, 2023)
Hematologic malignancies, including multiple myeloma (MM), promote systemic immune dysregulation resulting in an alteration and increased plasticity of myeloid cell subsets. To determine the heterogeneity of the myeloid cell compartment in the peripheral blood of patients with MM, we performed a detailed investigation of the phenotype and function of myeloid subpopulations. We report that a subset of MM patients exhibits a specific myeloid cell phenotype indicative of altered myelopoiesis characterized by significant changes in the properties of circulating granulocytic, monocytic, and eosinophilic populations. The subset, referred to as MM2, is defined by a markedly elevated level of CD64 (FcRI) on the surface of circulating neutrophils. Compared to healthy controls or MM1 patients displaying intermediate levels of CD64, neutrophils from MM2 patients exhibit a less differentiated phenotype, low levels of CD10 and CXC chemokine receptor 2 (CXCR2), increased capacity for the production of mitochondrial reactive oxygen species, and an expansion of CD16 neg immature neutrophil subset. Classical and patrolling monocytes from MM2 patients express elevated levels of CD64 and activation markers. MM2 eosinophils display lower levels of C-C Chemokine receptor 3 (CCR3), Toll-like receptor 4 (TLR4, CD284), and tissue factor (TF, CD142). The MM2 (CD64 high) phenotype is independent of age, race, sex, and treatment type. Characteristic features of the MM2 (CD64 high) phenotype are associated with myeloma-defining events including elevated involved/uninvolved immunoglobulin free light chain (FLC) ratio at diagnosis. Detailed characterization of the altered myeloid phenotype in multiple myeloma will likely facilitate the identification of patients with an increased risk of disease progression and open new avenues for the rational design of novel therapeutic approaches.